The way of the brave eaudiobook - Warren, Susan May (Global Search and Rescue, 2020)
Former pararescue jumper Orion Starr is haunted by the memory of a rescue gone wrong. He may be living alone in Alaska now, but the pain of his failure—and his injuries—has followed him there from Afghanistan. He has no desire to join Hamilton Jones's elite rescue team, but he also can't shirk his duty when the call comes in to rescue three lost climbers on Denali. Former CIA profiler and psychiatrist Jenny Calhoun's yearly extreme challenge with her best friends is her only escape from the guilt that has sunk its claws into her. As a consultant during a top-secret mission to root out the Taliban, she green-lighted an operation that ended in ambush and lives lost. When her cathartic climb on Denali turns deadly, she'll be forced to trust her life and the lives of her friends to the most dangerous of heroes—the man she nearly killed. Her skills and his experience are exactly what's needed to prevent another tragedy—but in order to truly set Orion free from his painful past, Jenny will have to reveal hers. They'll have to put their wounds behind them to survive, but at what cost? Leap into action with this high-octane, breakneck new series from bestselling author Susan May Warren.